Lightning related human casualties in Mongolia - Doljinsuren, Myagmar; Gomes, Chandima (IEEE, 2016)
Lightning related casualties collected by the Institute of Meteorology in Mongolia from 2003 to 2015 have been analyzed. Being a country with one of the lowest population density, Mongolia records a relatively high human death rate per unit population per year, 15.4 dptm yr-1, which is much higher than that of many countries with similar isokeraunic level. During this period 57 deaths and 58 injuries have been reported, thus death to injury ratio is nearly 1:1. Around 88% of both deaths and injuries has been reported to be occurred while the victim is in wild area, typically the low-grown slopes in steppe climate. Other 12% of the death and injury cases have been located either in open spaces within the village or inside the fabric enclosed houses known as ger. Nearly 80% of the gender known deaths are of males. Almost 100% of the deaths of which the time of incident is known has happened between noon and midnight. Almost all case of injuries have also been reported during the same period. About 80% of the age-reported deaths were of people below 30 years. Slightly more than 50% of the deaths and 54% of the injuries have been reported from Central province.